Cultivating Early Literacy: Impact on Grade One Academic Achievement - Casido, Wilma (Journal of Interdisciplinary Perspectives, 2024)
Teaching pupils to read requires patience, creativity, and a deep understanding of their learning styles. By fostering a supportive and engaging environment, educators can instill a lifelong love for reading in young learners. This study aimed to assess the Grade 1 pupils’ foundational literacy skills with their academic performance. It was conducted among the Grade 1 pupils of Zamboanguita District 2, Division of Negros Oriental, for the school year 2021–2022. The study utilized the descriptive-correlational research design and employed a standardized questionnaire provided by the Division Office. The statistical tools used are percentage, mean, mean percentage score, Pearson product-moment coefficient of correlation, and t-test for independent data. The study revealed that the Grade 1 pupils’ foundational literacy skills in listening comprehension, letter-sound identification, initial sound discrimination, and familiar word reading are just around the borderline of passing. It was also revealed that their academic performance based on their grades is satisfactory. Moreover, pupils’ foundational literacy skills are determinants of their’ academic performance.